Energy and quadratic invariants preserving methods for Hamiltonian systems with holonomic constraints - Li, Lei; Wang, Dongling (2020)
We introduce a new class of parametricization structure-preserving partitioned Runge-Kutta ( $α$ -PRK) methods for Hamiltonian systems with holonomic constraints. When the scalar parameter$α=0$ , the methods are reduced to the usual symplectic PRK methods like Shake-Rattle method or PRK schemes based on Lobatto IIIA-IIIB pairs, which can preserve all the quadratic invariants and the constraints. When$α≠ 0$ , the methods are also shown to preserve all the quadratic invariants and the constraints manifold exactly. At the same time, for any given consistent initial values$(p_{0}, q_0)$and small step size$h>0$ , it is proved that there exists$α^*=α(h, p_0, q_0)$such that the Hamiltonian energy can also be exactly preserved at each step. We provide a new variational formulation for symplectic PRK schemes and use it to prove that the parametrized PRK methods can preserve the quadratic invariants for Hamiltonian systems subject to holonomic constraints. The parametric$α$ -PRK methods are shown to have the same convergence rate as the usual PRK methods and perform very well in various numerical experiments.